MONEY FACTOR IN THE NOMINATION OF CHINESE-INDONESIAN WOMEN LEGISLATIVE CANDIDATES: A CASE OF LOCAL LEGISLATIVE ELECTION IN SEMARANG CITY, INDONESIA - Sweinstani, Mouliza K D (PEOPLE: International Journal of Social Sciences, 2019)
Financial capital associated with the ownership of money is an important factor in candidates’ nomination in an election. For candidates who have substantial financial capital, it is assumed that they can be easier to be elected. This argument can also be used to discuss the case of the nomination of Chinese-Indonesian Women. This study aims to explain how money is used by Chinese-Indonesian women candidates in Semarang City in the 2014 legislative election and how this factor can support their wining. Using qualitative research methods with primary data source obtained from in-depth interviews to four Chinese-Indonesian women candidates and elites from their bearer party in Semarang City, it is known that financial capital was used to finance each candidate's campaign needs. Financial capital they owned could also be their supremacy compared to other candidates that was promoted by them in the recruitment process within the party. Unfortunately, this capital had not been able to deliver all Chinese women candidate to be elected as MPs. Factors that support their wining were the socio-cultural closeness capital with voters and kinship ties with male elites.